An Operation Control Strategy for the Connected Maglev Trains Based on Vehicle-Borne Battery Condition Monitoring. (12th April 2018) - Zhang, Wenjing; Wei, Wenjun; Yang, Yifan; Nan, Nan
Abstract : Vehicle-borne battery condition is an important factor affecting the efficiency of the maglev train operation and other connected ones. To effectively eliminate the influence of the battery condition and improve the operation efficiency of the connected maglev trains, an operation control strategy is proposed to guarantee train operation safety. First, based on Internet of Things, a sensor network is designed to monitor vehicle-borne battery condition in each vehicle of the train. Second, the train Operation Control System collects battery data of all vehicles in a maglev train by Train Communication Network. Third, all connected maglev trains share the battery data via a 38 GHz directional Radio Communication System and adjust operation control strategy accordingly. Simulation results indicate that the proposed strategy can guarantee the operation safety of the connected maglev trains.